Structural, dynamical, and thermodynamical properties of carbon nanotube polycarbonate composites: a molecular dynamics study - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2012)
All-atom molecular dynamics simulations are performed on pure monomer and trimer of polycarbonate and their mixtures with different molecular weight percentages of embedded single walled carbon nanotubes at different temperatures to study the structural and dynamical properties of the composite system. The diffusion behaviors of monomer, trimer of polycarbonate and carbon nanotubes in composite matrices are investigated and compared with pure matrices in details. Both structural and dynamical properties indicate the weak interaction between the nanotubes and matrix molecules. The high tendency of nanotubes to form bundles is observed during simulation. The bundle formation free energy has been calculated from the potential of mean force calculations. The mechanism and energetics of bundle formation is explored in the atomistic scale. The formation of the carbon nanotube bundle is a favorable process in the oligomeric polycarbonate matrix.

Morphology and dynamics of carbon nanotube in polycarbonate carbon nanotube composite from dissipative particle dynamics simulation - Chakraborty, Souvik; Choudhury, Chandan Kumar; Roy, Sudip (Macromolecules, 2013)
Morphology and dynamics of carbon nanotube (CNT) in polycarbonate matrix with different mixing ratios are studied in mesoscale by using dissipative particle dynamics (DPD). We have used atomistic simulation to derive necessary interaction parameter for mesoscale DPD simulation for polycarbonate nanotube composite using Flory-Huggins theory. The diffusion and morphology of nanotubes in different concentrations (2%, 5%, 10%) are investigated. Diffusivity of nano tubes in polymer matrices is explored at different temporal regimes of simulation. Diffusion of nanotubes becomes significantly slow when bundling of nanotubes takes place. The bundle formation of nanotubes is observed in all of three mixtures with varying degrees of assembling and alignment Bundle size analysis is performed to study the extent of bundling affinity of CNTs in different filler concentrations. Size of the bundles of nanotubes is more in higher nanotube concentrations. In the 10% mixture percolation network is found to be formed by bundles of nanotubes.

Structure of nanorod assembly in the gyroid phase of diblock copolymer - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Diblock copolymers undergo microphase separation to form various microstructures, for example, lamellar, gyroid, cylindrical, cubic phases depending on compostion and segregation strength (Flory-Huggins parameter chi). Thus, it can act as template to organize doped nanomaterials into different 3D self-assembled structures located within the block copolymer matrix. Gyroid phase is One of the microstructures formed by block copolymer. It has a curved interfacial surface providing confinements throughout the matrix and thus can regulate the shape and sizes of self-assembled nanorods doped in it. Mesoscale simulation of model systems has been performed to explore the structure and dynamics of self-assembly of bundles formed by nanorods of different flexibilities in the gyroid phase of diblock copolymer matrix. Bundles of different shapes and sizes have been found to be formed depending on the nanorod bending flexibility and copolymer-nanorod interactions. The shape anisotropy (kappa(2)) and radius of gyration (R-g(2)) of bundles situated at different interfacial confining locations of block copolymer-matrices have been investigated as a function of nanorod flexibility and nanorod-diblock copolymer miscibility.

Phase diagram of self-assembled sophorolipid morphologies from mesoscale simulations - Sarkar, Sujit; Chakraborty, Souvik; Roy, Sudip (Journal of Molecular Liquids, 2018)
We have constructed a phase diagram from the self-assembled morphologies of linolenic acid sophorolipid in water by performing mesoscale simulations in different concentrations. The dependence of morphologies and its properties of the self-assembled structure as a function of the concentration of bolaamphiphile in water are investigated. Two hydrophilic head groups and one hydrophobic tail group of bolaamphiphile have been mapped to beads for mesoscale simulation. The interaction parameters between different beads are calculated using Flory-Huggins solution theory. Flory-Huggins x-parameters have been calculated from atomistic simulation and experimental data of pure components constituting linolenic acid sophorolipid. We have obtained different self-assembled morphologies depending upon the concentrations of sophorolipid in water. We have explored the arrangements of hydrophobic and hydrophilic groups of the sophorolipid chains in the different morphologies. The sophorolipid chains found to be present in different structural arrangements. The residence time and flip frequency of these lipids in different orientations have been calculated and discussed in this work. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bolaamphiphile; Flip frequency; Mesoscale simulation; Orientation of chains; Self-assembly